KESULITAN BELAJAR PADA SISWA SEKOLAH DASAR: STUDI KASUS DI SEKOLAH DASAR NEGERI AGOM - Permana, Alpin (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
Learning difficulties are conditions where one student experiences difficulties in learning in the field of study, the factors that cause, and the nature of learning difficulties at SD Negeri Agom. This research uses a quantitative descriptive approach. The research subjects included students of SD Negeri Agom. Data collection techniques used are interview, observation, and documentation methods. The research instruments used were interview guidelines and observation guidelines. The results showed that 1) the level of learning difficulty of SD Negeri Agom students was in the medium category, 2) the field of study that was difficult for students to study was mathematics, 3) the factors causing learning difficulties, 4) while the nature of the learning difficulties was temporary. By knowing the types of learning difficulties, teachers can choose the right, effective and efficient types of interventions to provide in helping students overcome learning difficulties.